(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Morphometric analysis is important in any hydrological investigation and it is useful in development and management of drainage basin. A systematic morphometric analysis helps to understand the liner, areal and relief aspects of the drainage basin. In the present study I‟ve focused mostly on the use of morphometric indices for prioritization of watershed for conservation and management. The present study area is Tavarja reservoir catchment located in Latur district of Maharashtra. It is part of river Godavari covering geographical area of 250.52 Km².Overall 72 micro watershed have been taken up for prioritization of sub watersheds for conservation planning. The drainage map of the study area is generated through SOI toposheet (1: 50000). Stream characteristics includes number and length of streams of different orders, drainage density, drainage frequency, bifurcation